Policies Concerning Sacred And Open Traditional Cultural Expressions: Tourism And Creative Economy In Bali Context - Dewi Kasih, Desak Putu; Dharmawan, Ni Ketut Supasti; Samsithawrati, Putu Aras; Dwijayanthi, Putri Triari; Dian Sawitri, Dewa Ayu; Krisna Yanti, A.A. Istri Eka (JATISWARA, 2023)
This study aims to elaborate on the policies regarding the protection of TCEs related to creative economy businesses in the tourism sector, and the implementation of these policies in Bali. The study uses a socio-legal research method by using statutes, conceptual, economic, and technological approaches. The study indicated that TCEs are transformed across generations in custodian communities that are not sacred can be categorized as open TCEs and can be developed to support tourism creative economy businesses. Meanwhile, the type of TCEs that are sacred can only be used by the community carrying them for sacred purposes, categorized as closed TCEs. The policies at the international, national, and local levels related to open TCEs have regulated access for it to be developed for creative economy businesses including the tourism sector as well as protection of benefit sharing for the community. Meanwhile, the Indonesia Copyright Law and Provisions on Communal Intellectual Property Data have not accommodated benefit sharing. In Bali, policy related to sacred TCE can be observed through the 2019 Joint Decree on the Strengthening and Protection of Balinese Sacred Dances that prohibits Balinese Sacred Dances from being performed outside of sacred purposes. The implementation of an inventory of the protection of TCEs in Bali has been carried out by the Office of the Ministry of Law and Human Rights of Bali Province in collaboration with the Regional Government in Bali including university, although has not been maximized due to the large variety of cultural expressions in the community.